The effect of timing of intravenous paracetamol on perioperative pain and cytokine levels following laparoscopic bariatric surgery, a randomized controlled trial. Issue 11 (25th September 2022) - Semyonov, Michael; Bartulovic, Anastasiya; Cohen, Nir; Berzon, Baruch; Fedorina, Ekaterina; Lerman, Sofia; Semionov, Anastasia; Friger, Michael; Acker, Asaf; Geftler, Alexander; Zlotnik, Alexander; Brotfain, Evgeni
Abstract: Objective: Bariatric surgeries involve manipulation of the viscera and are associated with significant postoperative pain. Paracetamol is a nonopioid analgesic with a rapid onset, and it is effective and safe. The study compared the effects of pre‐ and postincisional intravenous paracetamol administration for optimal postoperative pain management in patients undergoing bariatric surgeries. Methods: This is a prospective, double‐blinded, placebo‐controlled randomized clinical trial of adult patients, admitted electively for laparoscopic bariatric surgery. The patients were randomly divided into two groups. One group of patients was given paracetamol at the beginning of the operation, prior to the surgical incision, the other group of patients received the same treatment at the end of the operation. Results: Patients who were given preincisional intravenous paracetamol presented significantly lower visual analog scale (VAS) scores following the surgery compared with patients who were given intravenous paracetamol in the last 30 minutes of the operation (VAS, median [IQR] = 2 [2‐3] vs. 5 [3‐6]; p  < 0.001). They also required fewer postoperative opioids and tramadol (in milligrams, respectively, 1 [0‐5] vs. 7.5 [5‐10] and 300 [100‐400] vs. 400 [200‐500]) compared with later analgesia administration ( p  < 0.001 and p  = 0.03). The levels of inflammatory markers measured at fixed intervals from paracetamol administration were not statistically different between the study groups. Conclusion: Early analgesia with intravenous paracetamol, given before the surgical incision, may result in lower VAS scores postoperatively compared with the same treatment administered toward the end of the operation.